The influence of match location, quality of opposition, and match status on possession strategies in professional association football - Lago, C. (Journal of Sports Sciences, 2009)
The aim of this study was to examine the effects of match location, quality of opposition, and match status on possession strategies in a professional Spanish football team. Twenty-seven matches from the 2005-2006 domestic league season were notated post-event using a computerized match analysis system. Matches were divided into episodes according to evolving match status. Linear regression analysis showed that possession of the ball was greater when losing than when winning (P < 0.01) or drawing (P < 0.05), and playing against strong opposition was associated with a decrease in time spent in possession (P < 0.01). In addition, weighted mean percentage time spent in different zones of the pitch (defensive third, middle third, attacking third) was influenced by match status (P < 0.01) and match location (P < 0.05). A combination of these variables and their interactions can be used to develop a model to predict future possession in football. The findings emphasize the need for match analysts and coaches to consider independent and interactive potential effects of match location, quality of opposition, and match status during assessments of technical and tactical components of football performance. In particular, the findings indicate that strategies in soccer are influenced by match variables and teams alter their playing style during the game accordingly.